Development of a rapid method of analysing whole blood omega‐3 levels using a fingertip blood sample and measuring breast milk omega‐3 levels using automated methods. Issue 11 (November 2013) - Bell, Gordon; Gilhooly, Tom; Mackinlay, Elizabeth; Younger, Irene; McLellan, Ramsay; Dick, James
Abstract It is widely accepted that intake of n‐3 long‐chain polyunsaturated fatty acids (PUFA) can have positive benefits for human health, particularly for CVD, although recent evidence suggests similar benefits may exist over a wider range of inflammatory and lifestyle disorders. This study describes the development of a rapid whole blood finger tip analysis to measure n‐3 highly unsaturated fatty acids (HUFA) in human subjects.